PENGARUH EFEKTIVITAS SIA DAN SPI TERHADAP KUALITAS LKPD DIMODERASI OLEH KUALITAS SDM - Senda Yunita Leatemia; Yudi Iskandar Ely (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
Abstract This study aims to determine the effect of the effectiveness of accounting information systems and internal control systems on the quality of financial statements with the quality of human resources as a moderating variable. This research uses population studies or census studies. This study are primary data obtained from direct distribution of questionnaires. This result of the study partially show that the effectiveness of accounting information systems and internal control systems has an effect on the quality of financial statements. Analysis of moderating variables using the absolute different value approach shows that the quality of human resources is able to moderate the effectiveness of the accounting information system but is not able to moderate the internal control system on the quality of financial statements. Keywords: Effectiveness of Accounting Information System, Internal Control System, Quality of Financial Statement, and Quality of Human Resources.